Association of genetic variants of the Fat Mass and Obesity (FTO) gene and obesity in children - Oleksandr Abaturov; Anna Nikulina (Publicaciones Permanyer, 2024)
Introduction and Objectives: Single nucleotide variants (SNVs) of the gene associated with fat mass and obesity (FTO) make a significant contribution to the violation of energy metabolism and the development of obesity. Study the associations between SNVs of the FTO gene and the development of metabolic disorders in children with obesity. Methods: 252 obese children aged between six and 18 were examined. The main group (n = 152) represented children with metabolically unhealthy obesity (MUO). The control group (n = 100) consisted of children with metabolically healthy obesity (MHO). Whole genome sequencing (CeGat, Germany) was performed in 31 children from the main group and 21 children from the control group. Results: The association with the development of obesity is higher for the A allele rs2287142 (t = 2.29) and the T allele SNV rs17823223 (t = 6.34) compared to healthy individuals. Serum IL-6 levels in individuals with MHO depend on SNV rs2287142 (r = 0.73). The A allele of SNV rs1080312 is associated with basal hyperglycemia (r = 0.43) and impaired carbohydrate tolerance (r = 0.33), but negatively correlates with low serum cholesterol and low-density lipoprotein cholesterol (LDL-C) (r = -0.42 and r = -0.39, respectively). The T allele of SNV rs778691805 is associated with high levels of LDL-C in blood serum (r = 0.33). The T allele of SNV rs17823223 is negatively associated with basal hyperglycemia (r = -0.51) and directly correlates with high-density lipoprotein cholesterol (r = 0.33) (p < 0.05). Discussion: In obese children, SNV rs2287142 is associated with pro-inflammatory status and SNVs rs1080312, rs17823223, and rs778691805 of the FTO gene are associated with metabolic markers.